Nanocarriers for Inner Ear Disease Therapy - Xiaoxiang Xu (Frontiers Media S.A., 2021)
Hearing loss is a common disease due to sensory loss caused by the diseases in the inner ear. The development of delivery systems for inner ear disease therapy is important to achieve high efficiency and reduce side effects. Currently, traditional drug delivery systems exhibit the potential to be used for inner ear disease therapy, but there are still some drawbacks. As nanotechnology is developing these years, one of the solutions is to develop nanoparticle-based delivery systems for inner ear disease therapy. Various nanoparticles, such as soft material and inorganic-based nanoparticles, have been designed, tested, and showed controlled delivery of drugs, improved targeting property to specific cells, and reduced systemic side effects. In this review, we summarized recent progress in nanocarriers for inner ear disease therapy. This review provides useful information on developing promising nanocarriers for the efficient treatment of inner ear diseases and for further clinical applications for inner ear disease therapy.